Genetically transformed roots: From plant disease to biotechnological resource - Georgiev, Milen I. (2012)
Hairy root syndrome is a disease that is induced by Agrobacterium rhizogenes infection and characterized by a proliferation of excessively branching roots. However, in the past 30 years A. rhizogenes-mediated transformation has also provided a valuable platform for studying biosynthesis pathways in plants. Furthermore, the genetically transformed root cultures are becoming increasingly attractive, cost-effective options for mass-producing desired plant metabolites and expressing foreign proteins. Numerous proof-of-concept studies have demonstrated the feasibility of scaling up hairy-root-based processes while maintaining their biosynthetic potential. Recently, hairy roots have also shown immense potential for applications in phytoremediation, that is, plant-based decontamination of polluted environments. This review highlights recent progress and limitations in the field, and outlines future perspectives for the industrial exploitation of hairy roots.